Mendidik dengan Pendekatan Humanis dalam Bingkai Pendidikan Agama Katolik di Sekolah - Sitepanus Zebua; Sabar Berkat Hulu; Yohanes Jok Pendopo Laoli; Nur Asnayanti Bu’ulolo (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2026)
In this study, the researcher examines in depth the concept and application of various research approaches in various previous scientific studies. The research study material is theoretical studies and the results of previous research from books, national journals and international journals. The author uses data analysis with a descriptive qualitative approach. The results of the study show that Educating with a Humanist Approach in the Framework of Catholic Religious Education in Teacher Schools. It was found that educating with a humanist approach is very relevant in education, because what is fostered and faced is humans. Moreover, the research indicates that integrating humanist principles within the context of Catholic education can improve the emotional and psychological well-being of students, promoting a more compassionate and just educational environment. Educators who adopt this approach are encouraged to not only transmit knowledge but also cultivate personal relationships with their students, ensuring that their development as human beings is nurtured alongside their academic achievements.